Associations between muscle measures, survival, and toxicity in patients with limited stage small cell lung cancer. Issue 5 (28th July 2020) - Halvorsen, Tarje Onsøien; Valan, Christine Damgaard; Slaaen, Marit; Grønberg, Bjørn Henning
Abstract: Background: Standard treatment for patients with limited stage small cell lung cancer (LS SCLC) is concurrent platinum–etoposide chemotherapy and thoracic radiotherapy (TRT). Up to 30% of patients are cured, but severe toxicity is common, and we are not able to identify those who are cured or those who experience severe toxicity before chemoradiotherapy commences. Studies of other cancer patients show that low muscle mass and muscle radiodensity are associated with inferior survival and that a high drug dose per kilogram lean body mass (LBM) is associated with more toxicity, but this has not been investigated in LS SCLC. We analysed patients from a randomized trial comparing two schedules of TRT ( n  = 157) to investigate the prognostic and predictive role of these muscle measures in LS SCLC. Methods: Patients from a trial comparing once daily hypofractionated with twice daily hyperfractionated TRT were analysed. The skeletal muscle index (SMI), skeletal muscle radiodensity (SMD), and LBM were assessed from baseline computed tomography scans at the L3 level using the SliceOMatic software. Results: Images at the L3 level were available for 122 patients (77.7%). Median age was 64 years, 18% had performance status 2, and 38% had stage III. Grade 3–4 toxicity was observed in 89%, and 5% died from treatment‐related side effects. Overall, the median overall survival was 23 months, and the 5 year survival was 25%. Median LBM was 45.2 (range: 16–65) kg, the median SMI 44.8 (range: 29–77) cm 2 /m 2, and the median SMD 39.3 (range 16–62) HU. There were no significant associations between survival and any of the muscle measures in the univariable analyses (SMI: P  = 0.906, SMD: P  = 0.829) or in multivariable analyses adjusting for baseline characteristics (SMI: P  = 0.836, SMD: P  = 0.260). A higher cisplatin dose per kilogram LBM in the first course significantly increased the risk of grade 3–4 haematological toxicity ( P  = 0.011) and neutropenic infections ( P  = 0.012). Conclusions: Patients who received a high dose of cisplatin per kilogram LBM had more haematological toxicity and neutropenic infections than other patients. None of the muscle measures were independent prognostic factors for survival in our cohort of LS SCLC patients who underwent standard chemoradiotherapy.